Effects of switching from a dipeptidyl peptidase-4 inhibitor to oral semaglutide on glucose metabolism in patients with type 2 diabetes: protocol for a multicentre, prospective, randomised, open-label, parallel-group comparison study (the SWITCH-SEMA 2 study) - Kyu Yong Cho; Hiroki Yokoyama; Tatsuya Atsumi; Hiroshi Nomoto; Jun Takeuchi; So Nagai; Yoshio Kurihara; Shin Aoki; Akinobu Nakamura; Hideaki Miyoshi; Shinji Taneda; Ichiro Sakuma; et al. (BMJ Open)
Introduction Incretin-based therapies exert antihyperglycaemic effects in patients with type 2 diabetes (T2D) in a blood glucose concentration-dependent fashion. The first-in-class oral glucagon-like peptide-1 receptor agonist semaglutide has potent effects on glycaemic and weight control, but little evidence has been published for the superiority of semaglutide for glycaemic control in patients after switching from a dipeptidyl peptidase-4 (DPP-4) inhibitor. Therefore, we aim to verify the efficacy of oral semaglutide in patients with T2D being treated with a DPP-4 inhibitor.Methods and analysis This study is a multicentre, prospective, randomised, open-label, parallel-group trial. In total, 172 participants with T2D who have been treated with a DPP-4 inhibitor for more than 12 weeks and who have a glycated haemoglobin (HbA1c) level of 7.0%–9.9% will be randomised to continue using their existing DPP-4 inhibitor or switch to oral semaglutide for 24 weeks. Biochemical analyses and physical assessment will be performed, and adverse events will be recorded at baseline and at the end of the study. The primary endpoint will be the effect of oral semaglutide on the change in HbA1c. The secondary endpoints will be the mean changes in body weight, abdominal circumference, systolic and diastolic blood pressure (BP), pulse rate, the relationship between improvement of metabolic parameters including HbA1c and patient background characteristics, side effects and other laboratory parameters.Ethics and dissemination This will be the first study to compare the effects of switching from a DPP-4 inhibitor to oral semaglutide on glycaemic control in patients with T2D. The results will be disseminated in peer-reviewed journals and at scientific conferences. Hokkaido University Certified Review Board (CRB no.1180001) has approved the protocol (no. 020–013).Trial registration number UMIN000045270 in the University Hospital Medical Information Network; jRCT1011210032 in the Japan Registry of Clinical Trials.